Who Are the Living Dead? A theology of death, life after death - Gehman, Richard J. (Evangel Publishing House, 1999)
The author sets out to answer the pivotal question of who the living dead are, and in so doing opens the whole area of traditional African religion to the scrutiny of Scripture.